2007
DOI: 10.1161/strokeaha.106.469072
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Syndrome and the Risk of Ischemic Heart Disease and Stroke Among Japanese Men and Women

Abstract: The metabolic syndrome is a major determinant of ischemic cardiovascular disease among middle-aged Japanese men and women, in particular among smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
130
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 22 publications
9
130
1
1
Order By: Relevance
“…8 Traditionally, the metabolic syndrome involves obesity, 9 leads to a cluster of other cardiovascular risk factors and increases the risk of cardiovascular disease. [10][11][12][13][14][15][16][17] The American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) defined the metabolic syndrome as a constellation of cardiovascular risk factors including obesity, 5 whereas the criteria of the International Diabetes Federation (IDF) 6 were based on the presence of obesity. The metabolic syndrome, by the IDF criteria, is defined as a condition of obese persons with certain cardiovascular risk factors; thus, non-obese persons are not diagnosed with the metabolic syndrome, even if they have any of these cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…8 Traditionally, the metabolic syndrome involves obesity, 9 leads to a cluster of other cardiovascular risk factors and increases the risk of cardiovascular disease. [10][11][12][13][14][15][16][17] The American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) defined the metabolic syndrome as a constellation of cardiovascular risk factors including obesity, 5 whereas the criteria of the International Diabetes Federation (IDF) 6 were based on the presence of obesity. The metabolic syndrome, by the IDF criteria, is defined as a condition of obese persons with certain cardiovascular risk factors; thus, non-obese persons are not diagnosed with the metabolic syndrome, even if they have any of these cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although metabolic syndrome has been recognized as a risk factor for atherosclerotic diseases such as coronary heart disease (2,3) and ischemic stroke (4)(5)(6)(7)(8), genetic risk for ischemic stroke in individuals with metabolic syndrome has remained uncharacterized. Given that stroke is the leading cause of severe disability and the third leading cause of death, after heart disease and cancer, in western countries and Japan (9), the identification of biomarkers for stroke risk is important both for risk prediction and for intervention to avert future events.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal obesity was not an important factor for coronary plaque vulnerability in Japanese women with ACS, although it is important for Japanese ACS men. 20 Although MetS has been acknowledged as a risk factor for cardiovascular disease and mortality, [1][2][3] it occurs more frequently in men than in women. We recently demonstrated that MetS and carotid artery remodeling were independent predictors of multiple complex coronary plaques in Japanese ACS men, 20 and among the components of MetS, abdominal obesity and low HDL-C level were significant in Japanese ACS men with multiple complex plaques.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The third report of the National Cholesterol Education Program (NCEP) Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (ATP III) specifically underscores the importance of MetS and provides a working definition of this syndrome. 4 However, measuring waist circumference might be inappropriate for Japanese, so 8 Japanese societies established a definition of MetS for Japanese subjects, 5 but a recent study demonstrated that MetS, as defined by WHO, NCEP, NCEP revised, and the International Diabetes Federation, predicted cardiovascular mortality in men, but the prediction was weak for women.…”
mentioning
confidence: 99%